648 Im pretty sure if not let me know
You should multiply the numbers to get your solution. either 345*25 or 3 and 25
dose this help?
We use quadratic formula for that one
remember that √-1=i
so
for
ax^2+bx+c=0
![x=\frac{-b+/-\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%2B%2F-%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
so
given
5x^2-6x+2=0
a=5
b=-6
c=2
![x=\frac{-(-6)+/-\sqrt{(-6)^2-4(5)(2)}}{2(5)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-6%29%2B%2F-%5Csqrt%7B%28-6%29%5E2-4%285%29%282%29%7D%7D%7B2%285%29%7D)
![x=\frac{6+/-\sqrt{36-40}}{10}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B6%2B%2F-%5Csqrt%7B36-40%7D%7D%7B10%7D)
![x=\frac{6+/-\sqrt{-4}}{10}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B6%2B%2F-%5Csqrt%7B-4%7D%7D%7B10%7D)
![x=\frac{6+/-2i}{10}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B6%2B%2F-2i%7D%7B10%7D)
Answer:
22
Step-by-step explanation:
n² - m =
-5² - 3 =
25 - 3 = 22
If my answer is incorrect, pls correct me!
If you like my answer and explanation, mark me as brainliest!
-Chetan K